PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK PADA TEMA TUGASKU SEHARI-HARI KELAS II SD - Hanjani, Nurul Aulia; Silalahi, Beta Rapita; Surya, Muhammad Kafi (Joyful Learning Journal, 2023)
This development research aims to determine the feasibility of big book learning media on the theme of my daily tasks in class II SD. This research is a Research and Development (R&D) research with the 4D development model. The development steps taken by researchers are: 1) Pedefiisian stage (define), 2). Design stage, 3). Development stage, and 4). Dissemination stage with data collection techniques using a questionnaire. The data analysis technique uses descriptive qualitative. Validation was carried out by material experts, media experts, and learning experts. The overall results of the assessment by material experts obtained an average score of 78.75% with the criteria Valid (Eligible) to be used as learning media for grade II elementary school students on the theme of My Daily Tasks. The overall results of the assessment by media experts obtained an average score of 82% with very valid criteria to be used as learning media for grade II elementary school students on the theme of My Daily Tasks. And the overall results by learning experts obtained an average score of 88.75%. This percentage includes very valid criteria to be used as learning media in the learning activities of grade II elementary school students on the theme of My Daily Tasks.